2011
DOI: 10.1016/j.ijdevneu.2011.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Development of an animal model for chronic mild hyperhomocysteinemia and its response to oxidative damage

Abstract: The purpose of this study was to develop a chronic chemically induced model of mild hyperhomocysteinemia in adult rats. We produced levels of Hcy in the blood (30μM), comparable to those considered a risk factor for the development of neurological and cardiovascular diseases, by injecting homocysteine subcutaneously (0.03μmol/g of body weight) twice a day, from the 30th to the 60th postpartum day. Controls received saline in the same volumes. Using this model, we evaluated the effect of chronic administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 66 publications
1
20
0
Order By: Relevance
“…Plasma Hcy concentration in rats subjected to this treatment achieved levels similar to those described in the plasma of patients with mild hyperhomocysteinemia (30 lM) (Scherer et al, 2011). The animals were killed by decapitation 12 h after the last injection of Hcy and the cerebral cortex and CSF were removed.…”
Section: Chronic Mild Hyperhomocysteinemiamentioning
confidence: 77%
See 2 more Smart Citations
“…Plasma Hcy concentration in rats subjected to this treatment achieved levels similar to those described in the plasma of patients with mild hyperhomocysteinemia (30 lM) (Scherer et al, 2011). The animals were killed by decapitation 12 h after the last injection of Hcy and the cerebral cortex and CSF were removed.…”
Section: Chronic Mild Hyperhomocysteinemiamentioning
confidence: 77%
“…Ectonucleotidases are integral membrane proteins (Yegutkin, 2008), therefore, it is plausible to suggest that the oxidative damage in membrane lipids may alter the normal function of these enzymes. Indeed, previous study from our group showed that mild hyperhomocysteinemia increases thiobarbituric acid reactive substances (TBARS) levels, an index of lipid peroxidation (Halliwell, 2006), in cerebral cortex in rats (Scherer et al, 2011). Other study demonstrated that Hcy in vitro decreases ATP and ADP hydrolysis in rat platelets probably by oxidative stress since antioxidants prevented such effects (Zanin et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…DL-Hcy was dissolved in 0.9% normal saline and the pH value was adjusted to 7.4. According to the dosage previously reported [9], subcutaneous injection of Hcy (0.03 umol/g) was carried out twice per day with an 8-hour interval, from the first day after the establishment of TNBS/ethanol-induced colitis model. Hcy injection was continued at this rate for 30 days.…”
Section: Methodsmentioning
confidence: 99%
“…DL-Hcy (SigmaAldrich Chemical Co., USA) was dissolved in 0.9 % normal saline and the pH value was adjusted to 7.4. Subcutaneous injection of Hcy (0.03 lmol g -1 ) was conducted twice per day with an 8-h interval from the first day after TNBS/ethanol administration through the end of thirty-day study [16]. The rats were randomly divided into 4 groups: …”
Section: Animals and Treatmentsmentioning
confidence: 99%